On-farm assessment of fennel varieties in Rajasthan - D Singh, M L Meena, (Journal of Spices and Aromatic Crops, 2013)
Fennel varieties viz., RF-205, RF-125, RF-145, RF-178 and NRCSS-AF1 with the recommended package of practices were evaluated in 120 farmers’ field from eight adopted villages of Pali district of Rajasthan. The results of the study indicated that under diversified agro-climatic conditions, three varieties of fennel viz., NRCSS-AF1, RF-205 and RF-125 were promising over local check with higher B : C ratio of 2.21, 2.02 and 1.63, respectively.